ANALISIS KEPUASAN TAMU TERHADAP PRODUK KAMAR BERDASARKAN GEOGRAPHICAL MARKET SEGMENT (STUDI PADA HOTEL DI KAWASAN WISATA UBUD) - I Gusti Agung Gede Witarsana (JURNAL BISNIS HOSPITALITI, 2017)
This study is aimed to determine and identify the level of guest satisfaction of hotel room products based on the perception of each geographical market segment. Market is divided by geographic segmentation due to the fact that buying behavior is influenced by the place where the consumers live and work including their culture, tradition, politic, climate. This fact affects some hotels to make adjustments of product, advertising, and sales as needed or based on characteristics of a particular country or region. By knowing the wishes of guests through their level satisfaction, the hotel management will be able to apply the appropriate and effective strategies according to the guest characteristics on a geographic area. Data of this study were collected through respondents using purposive sampling method. Searching for respondents with specific targets leading to the purpose of this research of 100 hotel guests from different geographic market segments such as America, Europe, Asia, Domestic (Indonesia), Australia. The calculation of satisfaction value scores using a scale of 1-10 adopted from the measurement scale used by booking.com. The result of this research found that the segment of the American market has thehighest satisfaction level of the other segment of the room product in the tourist area of Ubud with score of 9.4 while the segment of domestic market is the segment that gives the lowest score of 7.1.